2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7318500
|View full text |Cite
|
Sign up to set email alerts
|

A hand-held micro surgical device for contact force regulation against involuntary movements

Abstract: Involuntary movements such as heart beating in surgical environment and surgeon's tremor disturb a micro surgical manipulation and cause a risk of patient wound. Although the delicate operation is performed by a skilled surgeon, the sensitivity of the surgeon is limited to quantify the range of safe contact forces. In this paper, we developed a compact hand-held surgical device to maintain a required contact force to maintain a required contact force using a custom force sensor and a linear delta mechanism. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Furthermore, such mechanical coupling between the tool handle and tip for actuation challenges the integration of the tool with many of the available systems for robot-assisted surgery as it can easily interfere with the operation of the attached robotic system. To address these issues, the design goal in our work has been devising a compact, lightweight and modular unit that can be controlled independently and remotely when necessary regardless of its site of attachment (such as a manual tool handle, a handheld micromanipulator [2428,40] or a teleoperated/cooperatively-controlled robot [1923,29]), resulting in the motorized micro-forceps shown in Fig. 1b.…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, such mechanical coupling between the tool handle and tip for actuation challenges the integration of the tool with many of the available systems for robot-assisted surgery as it can easily interfere with the operation of the attached robotic system. To address these issues, the design goal in our work has been devising a compact, lightweight and modular unit that can be controlled independently and remotely when necessary regardless of its site of attachment (such as a manual tool handle, a handheld micromanipulator [2428,40] or a teleoperated/cooperatively-controlled robot [1923,29]), resulting in the motorized micro-forceps shown in Fig. 1b.…”
Section: Designmentioning
confidence: 99%
“…During this time, various teleoperated [1921,29], cooperatively-controlled [22,23] and handheld [2428,40,57] robotic devices have been proposed with the common goal of suppressing involuntary motion components, such as the physiological hand tremor of the surgeon. These systems were shown to improve the tool manipulation accuracy in studies using artificial phantoms and animal models, and therefore posed the potential to facilitate the safety and performance of the surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to provide a more precise tool manipulation in vitreoretinal surgery, various robotic systems have been developed during the past 20 years [ 27 ]. These research platforms include teleoperated devices [ 28 , 29 , 30 , 31 , 32 ], cooperatively-controlled systems [ 33 , 34 ], injectable ocular microrobots [ 35 , 36 ], or handheld tools [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ], and mostly shared the common goal of suppressing involuntary components of motion, such as the physiological hand tremor of the operator. Studies have now shown improved precision during procedures performed in artificial phantoms and animal models [ 18 ], and the potential to facilitate a safer operation on the extremely delicate retinal tissues during human surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In microsurgery, specifically in stapedectomy, integration of fiber Bragg grating (FBG) strain sensors on a micro-forceps enabled the first time quantification of forces involved in crimping of a stapes prosthesis, which ranged from 2.4 N to 5.2 N [ 53 ]. Based on a monolithic structure flexure and photo-sensors, a compact axial force sensor was developed providing a force resolution of 0.48 N [ 54 ], and was shown to properly work with a handheld robotic device to maintain a fixed contact force (200 and 400 mN) at the tool tip [ 42 ]. Recently, a strain-gauge-based force-sensing bipolar forceps was developed and used to measure axial and planar forces ranging up to 1.20 N during neurosurgical tasks in cadaveric brain experiments [ 55 ].…”
Section: Introductionmentioning
confidence: 99%